Plate 109: Device for two men to drain water from a marsh or foundation - Ramelli, Agostino (Le diverse et artificiose machine del capitano Agostino Ramelli, 1588)
Mechanics: hand crank; gated-lobe rotary pump.
Keywords: Pumping machinery; Rotary pumps; Machinery; Hand pumps